Two-component polyurethane resin adhesive for circuit board and preparation process thereof

By using a two-component polyurethane resin adhesive in circuit board adhesive, combined with the blending system of fluoroacrylate and furan resin and the use of other modifiers, the problem of insufficient high temperature resistance and wettability in circuit board applications is solved, and efficient wetting and dispersion and high temperature resistance are achieved, and the film formation is uniform.

CN116179142BActive Publication Date: 2025-03-21JIANGXI RONGHUI ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310176807.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-03-21
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

The existing polyurethane resin adhesives are insufficient in high temperature resistance in circuit board applications and poor wetting and permeability of materials, limiting their application in circuit boards.

Method used

The preparation method of two-component polyurethane resin adhesive is adopted to prepare a stable blending system by using fluoroacrylate and furan resin, and combined with the use of hydroxypropyl acrylate and N-(methoxymethyl)-2-acrylamide, the wetting and dispersion of the resin and high temperature resistance are enhanced, and the uniformity of the curing process is improved by hydrotalcite-modified aluminum trioxide as a catalyst.

Benefits of technology

It significantly improves the wetting and dispersion and permeability of polyurethane resin, enhances its high temperature resistance, and solves the problem of uneven film thickness, meeting the multiple performance requirements for adhesives in circuit board applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a two-component polyurethane resin adhesive for circuit boards and a preparation process thereof, including an A-component adhesive and a B-component adhesive, wherein the A-component adhesive includes a fluoroacrylate monomer, a furan resin, N-(methoxymethyl)-2-acrylamide, hydroxypropyl acrylate, nano-alumina, a dispersant, and an organic solvent; and the B-component adhesive includes 1,3-diisocyanate, glycerol, 3-phenylbenzoic acid, an organic tin catalyst, polyethylene oxide, a defoamer, and an organic solvent. The invention can prepare a two-component polyurethane resin adhesive with high temperature resistance and good wetting and dispersion effect, solves the problems of poor high temperature resistance and unsatisfactory wetting and penetration effect of polyurethane resin, and realizes its application in circuit boards.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a preparation process of a two-component polyurethane resin adhesive for circuit boards. Background Art

[0002] Generally, the substrate materials used in printed circuit boards can be divided into two categories: rigid substrate materials and flexible substrate materials. The most important type of rigid substrate materials is copper clad laminate. It is made of reinforcing materials (Reinforeing Material), impregnated with resin adhesive, dried, cut, and stacked into blanks, and then covered with copper foil, using steel plates as molds, and processed by high temperature and high pressure in a hot press.

[0003] Polyurethane (PU) adhesives are widely used in shoe sole bonding, luggage bonding, and automotive interior bonding due to their simple synthesis, readily available raw materials, and flexible molecular structure design. However, the high temperature resistance of polyurethane resin is not very ideal, which limits its application in circuit boards.

[0004] The fluorine-containing groups extend to the air / polymer interface, forming a good protective effect on the internal molecules of the polymer, so that the polymer has high anti-corrosion performance and thermal stability; the fluorine-containing acrylic polyurethane resin adhesive made from fluorine-containing acrylic monomers has excellent high temperature resistance, corrosion resistance and mechanical physical properties. However, due to the easy enrichment of fluorine-containing groups on the surface of the system and the electrostatic effect of the fluorine-containing acrylic polyurethane resin structure, the adhesive has poor wetting and permeability to the material. Therefore, the development of an adhesive for circuit boards with high temperature resistance and strong wetting and permeability is the main research direction of this industry. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing a two-component polyurethane resin adhesive with high temperature resistance and good wetting and dispersion effect. The technical scheme adopted comprises the following steps:

[0006] Step 1: Preparation of component A adhesive

[0007] The A component adhesive comprises the following components in parts by weight:

[0008] 42.49-63.07% of fluoroacrylate monomer, 7.51-8.93% of furan resin, 4.34-7.56% of N-(methoxymethyl)-2-acrylamide, 4.66-6.44% of hydroxypropyl acrylate, 2.33-3.87% of nano-alumina, 5.67-6.13% of dispersant, and the rest is organic solvent 1;

[0009] a) the total mass of the furan resin for preparing the adhesive component A is divided into three parts, the first part is 1%-10% of the total mass, the second part is 60%-75% of the total mass, and the third part is the remaining furan resin, the fluoroacrylate monomer (fluorinated acrylate monomer) of the weight percentage and the first part of the furan resin are added to the organic solvent 1, mixed evenly, the solution temperature is controlled to be 20-40° C., and the mixture is stirred at this temperature for 0.5-1h, the second part of the furan resin is added, and the mixture is stirred at this temperature for 1.5-2.5h, and then the third part of the furan resin is added, and the mixture is stirred at this temperature for 0.5-1h, and ultrasonic oscillation treatment is performed at the same time, and the obtained mixed solution A1 is set aside;

[0010] b) taking the weight percentage of N-(methoxymethyl)-2-acrylamide and hydroxypropyl acrylate, adding organic solvent 1, controlling the solution temperature to 20-40° C., stirring for 3-4 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution B1 for standby use;

[0011] c) stirring and mixing the mixed solution A1 obtained in step a), the mixed solution B1 obtained in step b), the remaining nano-alumina, the dispersant and the organic solvent 1 in the raw material of the adhesive component A, and heating them for 50 to 60 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the adhesive component A for standby use;

[0012] Further, the dispersant is polyacrylamide;

[0013] Furthermore, the organic solvent 1 is toluene or diethyl ether.

[0014] Step 2: Preparation of component B adhesive

[0015] The B component adhesive comprises the following components in parts by weight:

[0016] 24.56-40.29% of 1,3-diisobenzoate, 13.57-15.88% of glycerol, 4.43-5.12% of 3-phenylbenzoic acid, 12.44-16.71% of organic tin catalyst, 3.26-5.21% of polyethylene oxide, 4.74-7.79% of defoaming agent, and the rest is organic solvent 2.

[0017] 1) taking the weight percentage of 1,3-diisobenzocyanate, glycerol, and 3-phenylbenzoic acid, adding organic solvent 2 and mixing evenly, controlling the solution temperature to 25-40° C., keeping warm and stirring for 3-4 hours, and simultaneously performing ultrasonic oscillation treatment, and the obtained mixed solution A2 is used for standby;

[0018] 2) taking the organotin catalyst and polyethylene oxide in the weight percentage, adding organic solvent 2, controlling the solution temperature to 25-40° C., keeping the temperature and stirring for 1.5-2.5 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution B2 for standby use;

[0019] 3) stirring and mixing the mixed solution A2 prepared in step 1), the mixed solution B2 prepared in step 2), and the remaining defoamer and organic solvent 2 in the B component adhesive, and heating them for 50 to 60 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the B component adhesive for standby use;

[0020] Further, the defoaming agent is polydimethylsiloxane;

[0021] Furthermore, the organic solvent 2 is anhydrous ethanol or ether.

[0022] Step 3: Mechanically stir and mix the component A adhesive prepared in step 1 and the component B adhesive prepared in step 2 at a weight ratio of 1.2-1.8:1 to prepare a two-component polyurethane resin adhesive.

[0023] Furthermore, the preparation method of the organotin catalyst in step 2 is:

[0024] g) Hydrotalcite modified aluminum oxide

[0025] Calcium chloride, cobalt nitrate, and N'-(3-chlorophenyl)-N,N-dimethylurea are dissolved in deionized water to form solution A. Aluminum oxide is added, wherein the molar ratio of calcium chloride, cobalt nitrate, N'-(3-chlorophenyl)-N,N-dimethylurea and aluminum oxide is (3-17):(2-22):(150-200):(70-170); the solution A and aluminum oxide are transferred to a reaction kettle, crystallized at 220-310° C. for 12-24 hours, the reaction solution is filtered, washed until the pH of the eluent is 5.5-6.5, and the obtained hydrotalcite-modified aluminum oxide is dried at 220-310° C. for 12-18 hours.

[0026] h) Preparation of catalyst precursor

[0027] Dissolve tin methanesulfonate and bismuth roxatidine in deionized water to form solution B, immerse the hydrotalcite-modified Al2O3 obtained in step g) in solution B, let stand for 12-24 hours, and dry at 220-310° C. for 12-18 hours to obtain a catalyst precursor. The molar ratio of tin methanesulfonate, bismuth roxatidine and aluminum oxide modified by hydrotalcite is (15-25):(22-36):(800-1400).

[0028] i) Preparation of Catalyst

[0029] The catalyst precursor is reduced in a hydrogen atmosphere at 800-1100°C for 8-48 hours, and the rate of hydrogen introduction during the reduction process is 100-150 mL·min -1 , and the organotin catalyst is obtained.

[0030] The beneficial effects of the present invention are:

[0031] (1) The polyurethane glue formed by curing the fluoroacrylate monomer and the B component material can improve the insulation of the glue, but the storage stability is poor. The functional groups contained in the polyurethane resin formed by the fluoroacrylate monomer and the electrostatic effect generated by the resin structure make the pigment wetting and dispersibility poor. The main mechanism for the polymer to show extremely low wettability is the enrichment of fluorine on the surface. After the resin is formed into a film, the fluorine-containing part faces outward (air), and the surface tends to be crystalline and arranged tightly and regularly. The present invention prepares fluoroacrylate and furan resin into a stable blending system, thereby avoiding excessive aggregation density of fluorine elements, and the possibility of ester groups in the resin structure being exposed increases, thereby enhancing the surface wettability of the system.

[0032] (2) Hydroxypropyl acrylate can further improve the surface wetting properties of the formed polyurethane resin. The present invention heats and blends N-(methoxymethyl)-2-acrylamide and hydroxypropyl acrylate to form a mixed solution B with uniform internal crosslinking density, thereby further improving the high temperature resistance of the resin. Nano-alumina has a good ultraviolet shielding effect, thereby achieving the UV blocking performance of the synthetic resin.

[0033] (3) By activating the hydrogen bond donors in the mixed solution with 3-phenylbenzoic acid, the number of hydrogen bond connection points between the mixed solution and the formed polyurethane resin molecules increases, the number of hydrogen bonds formed in the system increases, the intermolecular force is enhanced, the glass transition temperature of the resin is increased, and the high temperature resistance of the adhesive is enhanced.

[0034] (4) The high temperature resistance of polyurethane resin is further improved by compounding organic tin catalyst with polyethylene oxide.

[0035] (5) When the polyurethane resin is pre-decomposed at high temperature, the double bonds in the system are cross-linked with the hydroxyl groups and the polyurethane resin monomers, and the interaction between the systems is enhanced, which increases the thermal decomposition temperature.

[0036] (6) In actual production tests, the inventors found that the polyurethane prepared by the A and B component adhesives has good wetting and dispersibility and strong high temperature resistance, but the film thickness formed by room temperature curing is uneven. The reason may be that the compatibility of the components of the adhesive is different, or the temperature or humidity changes in the environment may cause differences in the monomer conversion rate in different parts. Therefore, the inventors modified the catalyst and used aluminum oxide modified in situ with hydrotalcite as a carrier. The lattice induction effect of the hydrotalcite layer on the metal active center Sn and the auxiliary metal on the layer is used to improve the dispersion uniformity of the Sn active center. At the same time, the curing rate and monomer conversion rate of the two-component polyurethane resin are controlled. The problem of uneven film formation by curing of the glue liquid is solved.

[0037] (7) The thickness and internal structure of the resin film formed by curing the two-component polyurethane glue prepared by this technical solution at room temperature are uniform, which can meet the needs of some industries that have strict requirements on the uniformity of glue film formation. DETAILED DESCRIPTION

[0038] The present invention will be further described in detail below in conjunction with the embodiments.

[0039] Example 1

[0040] Step 1: Preparation of component A adhesive

[0041] The A component adhesive comprises the following components in parts by weight:

[0042] 52.78% of fluoroacrylate monomer, 8.22% of furan resin, 5.95% of N-(methoxymethyl)-2-acrylamide, 5.55% of hydroxypropyl acrylate, 3.10% of nano-alumina, 5.90% of polyacrylamide, and the rest is a mixture of toluene and ether in any proportion;

[0043] a) the total mass of the furan resin for preparing the adhesive component A is divided into three parts, the first part is 5.5% of the total mass, the second part is 67.5% of the total mass, and the third part is the remaining furan resin, the fluoroacrylate monomer (fluorinated acrylate monomer) and the first part of the furan resin are added to a toluene solution, mixed evenly, the solution temperature is controlled to 30° C., and stirred for 0.75 h, the second part of the furan resin is added, and the third part of the furan resin is added after stirring for 2 h, and stirred for 0.75 h, and ultrasonic oscillation treatment is performed at the same time, and the obtained mixed solution A1 is set aside;

[0044] b) taking the weight percentages of N-(methoxymethyl)-2-acrylamide and hydroxypropyl acrylate, adding ether, controlling the solution temperature to 30° C., stirring for 3.5 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution B1 for standby use;

[0045] c) stirring and mixing the mixed solution A1 obtained in step a), the mixed solution B1 obtained in step b), and the remaining nano-alumina, polyacrylamide and ether in the raw material of the adhesive component A, and heating them for 55 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the adhesive component A for standby use;

[0046] Step 2: Preparation of component B adhesive

[0047] The B component adhesive comprises the following components in parts by weight:

[0048] 32.43% of 1,3-diisobenzoate, 14.73% of glycerol, 4.78% of 3-phenylbenzoic acid, 14.58% of dibutyltin dilaurate, 4.24% of polyethylene oxide, 6.27% of polydimethylsiloxane, and the remainder is a mixture of anhydrous ethanol and ether in any proportion.

[0049] 1) taking the weight percentages of 1,3-diisobenzocyanate, glycerol and 3-phenylbenzoic acid, adding anhydrous ethanol solution and mixing evenly, controlling the solution temperature to 33° C., keeping the temperature and stirring for 3.5 hours, and simultaneously performing ultrasonic oscillation treatment, and the obtained mixed solution A2 is used for standby use;

[0050] 2) Take the above-mentioned weight percentage of dibutyltin dilaurate and polyethylene oxide, add ether, control the solution temperature to 33° C., keep stirring for 2 hours, and perform ultrasonic oscillation treatment at the same time, and prepare a mixed solution B2 for standby use;

[0051] 3) stirring and mixing the mixed solution A2 prepared in step 1), the mixed solution B2 prepared in step 2), and the remaining polydimethylsiloxane and ether in the B component adhesive, and heating them for 55 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the B component adhesive for standby use;

[0052] Step 3: Mechanically stir and mix the component A adhesive prepared in step 1 and the component B adhesive prepared in step 2 at a weight ratio of 1.5:1 to prepare a two-component polyurethane resin adhesive.

[0053] Example 2

[0054] Step 1: Preparation of component A adhesive

[0055] The A component adhesive comprises the following components in parts by weight:

[0056] 42.49% fluoroacrylate monomer, 8.93% furan resin, 7.56% N-(methoxymethyl)-2-acrylamide, 4.66% hydroxypropyl acrylate, 3.87% nano-alumina, 5.67% polyacrylamide, and the rest is toluene;

[0057] a) the total mass of the furan resin for preparing the adhesive component A is divided into three parts, the first part is 1% of the total mass, the second part is 75% of the total mass, and the third part is the remaining furan resin, the fluoroacrylate monomer (fluorinated acrylate monomer) of the weight percentage and the first part of the furan resin are added to toluene, mixed evenly, the solution temperature is controlled to 20° C., stirred at this temperature for 1 hour, the second part of the furan resin is added, stirred at this temperature for 1.5 hours, and then the third part of the furan resin is added, stirred at this temperature for 0.5 hours, and ultrasonic oscillation is performed at the same time, and the obtained mixed solution A1 is set aside;

[0058] b) taking the weight percentages of N-(methoxymethyl)-2-acrylamide and hydroxypropyl acrylate, adding toluene solution, controlling the solution temperature to 20° C., keeping the temperature and stirring for 3 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution B1 for standby use;

[0059] c) stirring and mixing the mixed solution A1 obtained in step a), the mixed solution B1 obtained in step b), and the remaining nano-alumina, polyacrylamide and toluene solution in the raw material of the adhesive component A, and heating them for 50 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the adhesive component A for standby use;

[0060] Step 2: Preparation of component B adhesive

[0061] The B component adhesive comprises the following components in parts by weight:

[0062] 40.29% 1,3-diisocyanate, 13.57% glycerol, 4.43% 3-phenylbenzoic acid, 12.44% dibutyltin dilaurate, 5.21% polyethylene oxide, 7.79% polydimethylsiloxane, and the rest is anhydrous ethanol.

[0063] 1) taking the weight percentages of 1,3-diisobenzocyanate, glycerol and 3-phenylbenzoic acid, adding anhydrous ethanol solution and mixing evenly, controlling the solution temperature to 40° C., keeping the temperature and stirring for 4 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution A2 for standby use;

[0064] 2) Take the above-mentioned weight percentage of dibutyltin dilaurate and polyethylene oxide, add anhydrous ethanol, control the solution temperature to 40° C., keep stirring for 2.5 hours, and perform ultrasonic oscillation treatment at the same time, and prepare a mixed solution B2 for standby use;

[0065] 3) stirring and mixing the mixed solution A2 prepared in step 1), the mixed solution B2 prepared in step 2), and the remaining polydimethylsiloxane and anhydrous ethanol in the B component adhesive, and heating them for 60 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the B component adhesive for standby use;

[0066] Step 3: Mechanically stir and mix the component A adhesive prepared in step 1 and the component B adhesive prepared in step 2 at a weight ratio of 1.2:1 to prepare a two-component polyurethane resin adhesive.

[0067] Example 3

[0068] Step 1: Preparation of component A adhesive

[0069] The A component adhesive comprises the following components in parts by weight:

[0070] 63.07% fluoroacrylate monomer, 7.51% furan resin, 4.34% N-(methoxymethyl)-2-acrylamide, 6.44% hydroxypropyl acrylate, 2.33% nano-alumina, 6.13% polyacrylamide, and the rest is ether;

[0071] a) the total mass of the furan resin for preparing the adhesive component A is divided into three parts, the first part is 10% of the total mass, the second part is 60% of the total mass, and the third part is the remaining furan resin, the fluoroacrylate monomer (fluorinated acrylate monomer) and the first part of the furan resin are added with ether in the said weight percentage, mixed evenly, the solution temperature is controlled to 40° C., stirred at this temperature for 0.5 h, the second part of the furan resin is added, stirred at this temperature for 1.5 h, and then the third part of the furan resin is added, stirred at this temperature for 0.5 h, and ultrasonic oscillation is performed at the same time, and the obtained mixed solution A1 is set aside;

[0072] b) taking the weight percentages of N-(methoxymethyl)-2-acrylamide and hydroxypropyl acrylate, adding ether, controlling the solution temperature to 40° C., stirring for 3 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution B1 for standby use;

[0073] c) stirring and mixing the mixed solution A1 obtained in step a), the mixed solution B1 obtained in step b), and the remaining nano-alumina, polyacrylamide and ether in the raw material of the adhesive component A, and heating them for 60 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the adhesive component A for standby use;

[0074] Step 2: Preparation of component B adhesive

[0075] The B component adhesive comprises the following components in parts by weight:

[0076] 24.56% 1,3-diisocyanate, 15.88% glycerol, 5.12% 3-phenylbenzoic acid, 16.71% dibutyltin dilaurate, 3.26% polyethylene oxide, 4.74% polydimethylsiloxane, and the rest is ether.

[0077] 1) Take the weight percentage of 1,3-diisocyanate, glycerol, and 3-phenylbenzoic acid, add ether and mix evenly, control the solution temperature to 25° C., keep warm and stir for 3 hours, and perform ultrasonic oscillation treatment at the same time, and prepare a mixed solution A2 for standby use;

[0078] 2) Take the weight percentage of dibutyltin dilaurate and polyethylene oxide, add ether, control the solution temperature to 25° C., keep warm and stir for 1.5 hours, and perform ultrasonic oscillation treatment at the same time, and prepare a mixed solution B2 for standby use;

[0079] 3) stirring and mixing the mixed solution A2 obtained in step 1), the mixed solution B2 obtained in step 2), and the remaining polydimethylsiloxane and ether in the B component adhesive, and heating them for 50 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the B component adhesive for standby use;

[0080] Step 3: Mechanically stir and mix the component A adhesive prepared in step 1 and the component B adhesive prepared in step 2 at a weight ratio of 1.8:1 to prepare a two-component polyurethane resin adhesive.

[0081] Example 4

[0082] a) Hydrotalcite modified aluminum oxide

[0083] Calcium chloride, cobalt nitrate, and N'-(3-chlorophenyl)-N,N-dimethylurea were dissolved in deionized water to form solution A. Aluminum oxide was added, wherein the molar ratio of calcium chloride, cobalt nitrate, N'-(3-chlorophenyl)-N,N-dimethylurea and aluminum oxide was 10:12:175:120; the solution A and aluminum oxide were transferred to a reactor, crystallized at 265° C. for 18 hours, the reaction solution was filtered, washed until the pH of the eluent was 6.0, and the obtained hydrotalcite-modified aluminum oxide was dried at 265° C. for 15 hours.

[0084] b) Preparation of catalyst precursor

[0085] Tin methanesulfonate and bismuth roxatidine are dissolved in deionized water to form solution B, and the hydrotalcite-modified Al2O3 obtained in step a) is immersed in solution B, left to stand for 18 hours, and dried at 265° C. for 15 hours to obtain a catalyst precursor. The molar ratio of tin methanesulfonate, bismuth roxatidine and aluminum oxide modified by hydrotalcite is 20:29:1100.

[0086] c) Preparation of Catalyst

[0087] The catalyst precursor was reduced in a hydrogen atmosphere at 950°C for 28 h, with the rate of hydrogen introduced during the reduction being 125 mL·min -1 , and an organotin catalyst is obtained.

[0088] Step 1: Preparation of component A adhesive

[0089] The A component adhesive comprises the following components in parts by weight:

[0090] 52.78% of fluoroacrylate monomer, 8.22% of furan resin, 5.95% of N-(methoxymethyl)-2-acrylamide, 5.55% of hydroxypropyl acrylate, 3.10% of nano-alumina, 5.90% of polyacrylamide, and the rest is a mixture of toluene and ether in any proportion;

[0091] 1) The total mass of the furan resin for preparing the adhesive component A is divided into three parts, the first part is 5.5% of the total mass, the second part is 67.5% of the total mass, and the third part is the remaining furan resin. The fluoroacrylate monomer (fluorinated acrylate monomer) and the first part of the furan resin are added to a toluene solution in the said weight percentage, mixed evenly, the solution temperature is controlled to 30° C., and stirred for 0.75 h at this temperature. The second part of the furan resin is added, stirred for 2 h at this temperature, and then the third part of the furan resin is added, stirred for 0.75 h at this temperature. Meanwhile, ultrasonic oscillation treatment is performed, and the obtained mixed solution A1 is set aside;

[0092] 2) Take the weight percentage of N-(methoxymethyl)-2-acrylamide and hydroxypropyl acrylate, add ether, control the solution temperature to 30° C., keep stirring for 3.5 hours, and perform ultrasonic oscillation treatment at the same time, and prepare a mixed solution B1 for use;

[0093] 3) stirring and mixing the mixed solution A1 obtained in step 1), the mixed solution B1 obtained in step 2), and the remaining nano-alumina, polyacrylamide and ether in the raw material of the adhesive component A, and heating them for 55 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the adhesive component A for standby use;

[0094] Step 2: Preparation of component B adhesive

[0095] The B component adhesive comprises the following components in parts by weight:

[0096] 32.43% of 1,3-diisocyanate, 14.73% of glycerol, 4.78% of 3-phenylbenzoic acid, 14.58% of an organic tin catalyst, 4.24% of polyethylene oxide, 6.27% of polydimethylsiloxane, and the rest is a mixture of anhydrous ethanol and ether in any proportion.

[0097] g) taking the above-mentioned weight percentages of 1,3-diisobenzocyanate, glycerol and 3-phenylbenzoic acid, adding anhydrous ethanol solution and mixing evenly, controlling the solution temperature to 33° C., keeping the temperature and stirring for 3.5 hours, and simultaneously performing ultrasonic oscillation treatment, and the obtained mixed solution A2 is used for standby use;

[0098] h) taking the organotin catalyst and polyethylene oxide in the weight percentage, adding ether, controlling the solution temperature to 33° C., keeping the temperature and stirring for 2 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution B2 for standby use;

[0099] i) stirring and mixing the mixed solution A2 obtained in step g), the mixed solution B2 obtained in step h), and the remaining polydimethylsiloxane and ether in the B component adhesive, and heating them for 55 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the B component adhesive for standby use;

[0100] Step 3: Mechanically stir and mix the component A adhesive prepared in step 1 and the component B adhesive prepared in step 2 at a weight ratio of 1.5:1 to prepare a two-component polyurethane resin adhesive.

[0101] Comparative Example 1

[0102] The difference between this comparative example and Example 1 is that the A component adhesive does not use furan resin.

[0103] Comparative Example 2

[0104] The difference between this comparative example and Example 1 is that the A component adhesive does not use N-(methoxymethyl)-2-acrylamide.

[0105] Comparative Example 3

[0106] The difference between this comparative example and Example 1 is that the A component adhesive does not use hydroxypropyl acrylate.

[0107] Comparative Example 4

[0108] The difference between this comparative example and Example 1 is that during the preparation of the A component adhesive, the furan resin is added at one time.

[0109] Comparative Example 5

[0110] The difference between this comparative example and Example 1 is that the B component adhesive does not use glycerin.

[0111] Comparative Example 6

[0112] The difference between this comparative example and Example 1 is that the B component adhesive does not use 3-phenylbenzoic acid.

[0113] Comparative Example 7

[0114] The difference between this comparative example and Example 1 is that the B component adhesive does not use polyethylene oxide.

[0115] Comparative Example 8

[0116] The difference between this comparative example and Example 1 is that the adhesive component A and the adhesive component B are mechanically stirred and mixed at a weight ratio of 1.1:1.

[0117] Comparative Example 9

[0118] The difference between this comparative example and Example 1 is that the adhesive component A and the adhesive component B are mechanically stirred and mixed at a weight ratio of 1.9:1.

[0119] Comparative Example 10

[0120] The difference between this comparative example and Example 4 is that the molar ratio of calcium chloride, cobalt nitrate, N'-(3-chlorophenyl)-N,N-dimethylurea and aluminum oxide is 3:22:150:70, and the molar ratio of tin methanesulfonate, roxatidine bismuth salt and hydrotalcite-modified aluminum oxide is 15:36:800.

[0121] Comparative Example 11

[0122] The difference between this comparative example and Example 4 is that the molar ratio of calcium chloride, cobalt nitrate, N'-(3-chlorophenyl)-N,N-dimethylurea and aluminum oxide is 17:2:200:170, and the molar ratio of tin methanesulfonate, roxatidine bismuth salt and hydrotalcite-modified aluminum oxide is 25:22:1400.

[0123] Comparative Example 12

[0124] The difference between this comparative example and Example 4 is that during the process of hydrotalcite modification of aluminum oxide, the solution A and aluminum oxide are transferred to a reactor, crystallized at 210° C. for 18 hours, the reaction solution is filtered and washed until the pH of the eluent is 5.0, and the obtained hydrotalcite-modified aluminum oxide is dried at 210° C. for 16 hours.

[0125] Comparative Example 13

[0126] The difference between this comparative example and Example 4 is that during the process of hydrotalcite modification of aluminum oxide, the solution A and aluminum oxide are transferred to a reactor, crystallized at 320° C. for 18 hours, the reaction solution is filtered and washed until the pH of the eluent is 7.0, and the obtained hydrotalcite-modified aluminum oxide is dried at 320° C. for 16 hours.

[0127] Comparative Example 14

[0128] The difference between this comparative example and Example 4 is that in the process of preparing the catalyst precursor, the hydrotalcite-modified Al2O3 is immersed in solution B, left to stand for 16 hours, and dried at 210°C for 16 hours.

[0129] Comparative Example 15

[0130] The difference between this comparative example and Example 4 is that in the process of preparing the catalyst precursor, the hydrotalcite-modified Al2O3 is immersed in solution B, left to stand for 16 hours, and dried at 320°C for 16 hours.

[0131] This experiment uses the cyclic thermal differential scanning method (DCS) to determine the high temperature resistance of the polyurethane adhesive. Thermogravimetric experimental conditions: weigh about 15 mg of the sample, in a high-purity inert atmosphere, the flow rate of the inert gas is controlled at 45 mL / min to 65 mL / min, the heating rate is controlled at 10 ° C / min, and the thermogravimetric analysis temperature range is 0 ° C to 800 ° C. Determine the temperature T when the weight of the sample begins to lose during the temperature increase process to determine the high temperature resistance of the polyurethane adhesive. The experimental results show that the prepared solvent-free two-component polyurethane adhesive begins to experience heat loss at around 400 ° C, proving that the polyurethane adhesive has excellent high temperature resistance.

[0132] The wettability of polyurethane adhesive to materials is determined by an interference-based contact angle optical measurement method. Contact angle measurement method: select a glass fiber cloth base with a droplet to be tested; use a QXOmno151 monochromator to illuminate the droplet to be tested, thereby generating interference fringes on the surface of the droplet to be tested; count the number of fringes moving k in the time interval when the wavelength of the monochromatic light emitted by the monochromator changes from λ to λ+Δλ; obtain the height h of the droplet to be tested by the number of fringes moving k, the refractive index n of the droplet to be tested, the wavelength λ of the light source, and the wavelength change Δλ; measure the top-view diameter d of the projection area of ​​the droplet to be tested on the plane of the glass fiber cloth base in a direction perpendicular to the plane of the glass fiber cloth base; obtain the contact angle θ of the droplet to be tested by the height h and the top-view diameter d of the droplet to be tested.

[0133]

[0134]

[0135] θ=0°, completely wetting; θ<90°, wetting; θ>90°, no wetting; θ=180°, completely no wetting.

[0136] Apply the two-component polyurethane resin adhesive evenly on the substrate, cure it at 20-30℃ for 4-5h, measure the film thickness (1nm-3.5mm) on the substrate surface with Filmetrics F20, record all the measured values, and calculate the film thickness uniformity value after data processing. Specific measurement point selection method: The substrate is a 300×400mm rectangular sheet. The measurement point selection is to first determine the midpoint of the diagonal as the central measurement point, and then select four points on the diagonal at a distance of 100 meters.

[0137] The point 200mm from the center measurement point is used as the measurement point. Film thickness uniformity S of the substrate i :

[0138]

[0139] Where: S i —Film thickness uniformity; T i—Measurement value of each measurement point in the substrate, in micrometers (μm);

[0140] Table 1 Comparison of indicators of Examples 1 to 4 of the present invention and Comparative Examples 1 to 8

[0141]

[0142]

[0143] Table 2 Comparison of indicators of Examples 1 to 4 of the present invention and Comparative Examples 10 to 15

[0144]

[0145]

[0146] It can be seen from the data in Table 1 combined with the technical parameters of the embodiments and comparative examples that the present invention can significantly improve the wetting, dispersibility and permeability of polyurethane resin to materials by preparing fluoroacrylate and furan resin into a stable blending system under a specific process; hydroxypropyl acrylate further improves the wetting and dispersibility of the resin, and together with N-(methoxymethyl)-2-acrylamide, enhances the high temperature resistance of the resin; the B component adhesive activates the hydrogen bond donor in the mixed solution by 3-phenylbenzoic acid, and the high temperature resistance of the resin is significantly enhanced; the difference in compatibility of the components of the A and B component adhesives during the curing process leads to uneven thickness of the adhesive film after adding a conventional catalyst. The present invention solves this problem by using an organic tin catalyst prepared by the process of the present invention, and prepares an adhesive with good wetting and dispersibility, high temperature resistance and uniform film formation.

Claims

1. A two-component polyurethane resin adhesive for a circuit board, comprising an A-component adhesive and a B-component adhesive, characterized in that: The adhesive component A is composed of the following components in parts by weight: 42.49-63.07% of fluoroacrylate monomer, 7.51-8.93% of furan resin, 4.34-7.56% of N-(methoxymethyl)-2-acrylamide, 4.66-6.44% of hydroxypropyl acrylate, 2.33-3.87% of nano-alumina, 5.67-6.13% of dispersant, and the rest is organic solvent 1; the adhesive component B is composed of the following components in parts by weight: 24.56-40.29% of 1,3-diisocyanate, 13.57-15.88% of glycerol, 4.43-5.12% of 3-phenylbenzoic acid, 12.44-16.71% of catalyst, 3.26-5.21% of polyethylene oxide, 4.74-7.79% of defoaming agent, and the rest is organic solvent 2; Wherein, the weight ratio of the adhesive component A to the adhesive component B is 1.2-1.8:

1.

2. A two-component polyurethane resin adhesive for a circuit board as claimed in claim 1, characterized in that: The preparation method of the A component adhesive is as follows: a) the total mass of the furan resin for preparing the adhesive component A is divided into three parts, the first part is 1%-10% of the total mass, the second part is 60%-75% of the total mass, and the third part is the remaining furan resin, the fluoroacrylate monomer and the first part of the furan resin are added to the organic solvent 1 in the weight percentage, mixed evenly, the solution temperature is controlled to be 20-40° C., and stirred for 0.5-1h at this temperature, the second part of the furan resin is added, and the third part of the furan resin is added after stirring for 1.5-2.5h at this temperature, and the mixture is stirred for 0.5-1h at this temperature, and ultrasonic oscillation treatment is performed at the same time, and the obtained mixed solution A1 is set aside; b) taking the weight percentage of N-(methoxymethyl)-2-acrylamide and hydroxypropyl acrylate, adding organic solvent 1, controlling the solution temperature to 20-40° C., stirring for 3-4 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution B1 for standby use; c) stirring and mixing the mixed solution A1 obtained in step a), the mixed solution B1 obtained in step b), the remaining nano-alumina, the dispersant and the organic solvent 1 in the raw material of the adhesive component A, and heating them for 50 to 60 minutes, and simultaneously performing ultrasonic oscillation treatment to obtain the adhesive component A.

3. A two-component polyurethane resin adhesive for circuit boards as claimed in claim 1, characterized in that: The preparation method of the B component adhesive is as follows: 1) taking the weight percentage of 1,3-diisocyanate, glycerol and 3-phenylbenzoic acid, adding organic solvent 2 and mixing evenly, controlling the solution temperature to 25-40° C., keeping warm and stirring for 3-4 hours, and simultaneously performing ultrasonic oscillation treatment, and preparing a mixed solution A2 for standby use; 2) Take the catalyst and polyethylene oxide in the weight percentage, add organic solvent 2, control the solution temperature to 25-40° C., keep warm and stir for 1.5-2.5 hours, and perform ultrasonic oscillation treatment at the same time, and prepare a mixed solution B2 for standby use; 3) The mixed solution A2 prepared in step 1), the mixed solution B2 prepared in step 2), and the remaining defoamer and organic solvent 2 in the B component adhesive are stirred, mixed, and heated for 50 to 60 minutes, and ultrasonically shaken to obtain the B component adhesive.

4. A two-component polyurethane resin adhesive for a circuit board as claimed in claim 1, characterized in that: The organic solvent 1 is toluene or diethyl ether, and the organic solvent 2 is anhydrous ethanol or diethyl ether.

5. A two-component polyurethane resin adhesive for circuit boards as claimed in claim 1 or 2, characterized in that: The dispersant is polyacrylamide.

6. A two-component polyurethane resin adhesive for circuit boards as claimed in claim 1 or 3, characterized in that: The defoaming agent is polydimethylsiloxane.

7. A two-component polyurethane resin adhesive for circuit boards as claimed in claim 3, characterized in that: The catalyst of the B component adhesive is an organic tin catalyst, and its preparation method is as follows: g) Hydrotalcite modified aluminum oxide Calcium chloride, cobalt nitrate, and N'-(3-chlorophenyl)-N,N-dimethylurea are dissolved in deionized water to form solution A, and aluminum oxide is added, wherein the molar ratio of calcium chloride, cobalt nitrate, N'-(3-chlorophenyl)-N,N-dimethylurea and aluminum oxide is (3-17):(2-22):(150-200):(70-170); the solution A and aluminum oxide are transferred to a reaction kettle, crystallized at 220-310° C. for 12-24 hours, the reaction solution is filtered, washed until the pH of the eluent is 5.5-6.5, and the obtained hydrotalcite-modified aluminum oxide is dried at 220-310° C. for 12-18 hours; h) Preparation of catalyst precursor Dissolve tin methanesulfonate and bismuth roxatidine in deionized water to form solution B, immerse the hydrotalcite-modified Al2O3 obtained in step g) in solution B, let stand for 12-24 hours, and dry at 220-310°C for 12-18 hours to obtain a catalyst precursor, wherein the molar ratio of tin methanesulfonate, bismuth roxatidine and hydrotalcite-modified aluminum oxide is (15-25):(22-36):(800-1400); i) Preparation of Catalyst The catalyst precursor is reduced in a hydrogen atmosphere at 800-1100°C for 8-48 hours, and the rate of hydrogen introduction during the reduction process is 100-150 mL·min -1 , and the organotin catalyst is obtained.

8. A method for preparing a two-component polyurethane resin adhesive for a circuit board as claimed in claim 1, characterized in that: The component A adhesive and the component B adhesive are mechanically stirred and mixed at a weight ratio of 1.2-1.8:1 to prepare a two-component polyurethane resin adhesive.

Citation Information

Patent Citations

  • Epoxy resin two-component polyurethane adhesive and preparation method thereof

    CN105419714A

  • High performance two-component polyurethane pressure sensitive adhesive and preparation method and application thereof

    CN108949088A